Sistem Pakar Menggunakan Metode Forward Chaining dalam Mengidentifikasi Penyakit Kambing - Putri Alicia (SEULANGA SYSTEM PUBLISHER, 2022)
Goats are one of the various types of animals that are widely kept and then traded because many can be utilized from goats. Disease checks on goats are not carried out regularly by breeders, especially if the breeders are still unfamiliar with raising goats, thus making goats susceptible to disease. This makes it difficult for farmers to handle due to limited knowledge. The limitation of veterinarians is also one of the problems that are often encountered in various regions. This study aims to analyze the disease in goats using the Forward Chaining method based on the symptoms and design an Expert System in measuring the accuracy of identifying diseases in goats. The data needed during this study were disease data in goats, symptom data and data solutions or treatments needed to make decisions that were sourced from veterinarians from the Pekanbaru City Agriculture and Livestock Service and one of the Veterinary Clinics in Pekanbaru City. Based on the data provided by the expert, the expert has a decision-making mode, which is to collect facts first to reach a conclusion or decision, so the Forward Chaining method can be used to conduct this research. The stages of data processing include preparing input data, expert decision tables, determining rules, conducting tracking processes, making decision trees and tracking results. The results obtained were successful in analyzing the symptoms and being able to determine diseases related to identifying diseases in goats so that solutions and initial steps for handling them could be determined. The results of trials conducted by comparing the data with the system that has been designed have a very good level of accuracy.